Assessment of fracture stability following modified minimally invasive reduction osteosynthesis system (MIROS) fixation for Neer 2 and 3-Part proximal humeral fractures - Osam Mohamed Metwally; Ahmed Hatem Farhan; Mahmoud Abdo Mahmoud; Hossam Fathi Mahmoud; Fahmy Samir Fahmy (BMC Musculoskeletal Disorders)
Abstract Background Conservative management for elderly proximal humeral fractures is an acceptable option, but the fracture stability is dubious. The purpose of this study was to investigate fracture stability and functional outcomes after modified minimally invasive reduction osteosynthesis system (MIROS) and non-surgical treatment for Neer two and three-part proximal humeral fractures in elderly patients. Methods Elderly Patients with two and three-part proximal humeral fractures who underwent modified MIROS fixation and non-operative management were retrospectively included. The Constant-Murley score, and the range of shoulder forward elevation were measured for functional assessment, while the radiological humeral head height (HHH) and humeral shaft angle (HSA) were used to verify the fracture stability. The variables in both treatment groups were compared using a two-tailed t test for independent means, with a p value of less than 0.05 denoting a significant difference. Results Forty-two patients were consecutively included, with a mean follow-up of 24.05 ± 3.9 months for the modified MIROS group and 24.67 ± 4.5 months for the non-operative group. The modified MIROS group had statistically significant improvements in the Constant score and shoulder forward flexion (p = 0.0001), with a lower complication rate (14.3% vs. 52.3%). Moreover, the average changes in the radiological HSA and HHH were lower in the modified MIROS group at the one-year follow-up (p = 0.00001). Conclusions Modified MIROS is recommended as an alternative to conservative treatment for Neer 2 and 3-part proximal humeral fractures in elderly, medically unfit patients. It is a minimally invasive procedure that provides adequate fracture stability and permits early shoulder motion, with satisfactory functional and radiologic outcomes and fewer complications. Level of evidence Retrospective comparative cohort; level of evidence (III).